Microeconomic Theory - Wang, Susheng (Springer Texts in Business and Economics, 2018)
This book covers microeconomic theory at the Master's and Ph.D levels for students in business schools and economics departments. It concisely covers major mainstream microeconomic theories today, including neoclassical microeconomics, game theory, information economics, and contract theory.